Behavior of Tether for Captive Stratosphere Platform Using Airship. (2015) - Chiba, Kazuhisa; Satori, Shin; Mitsuhashi, Ryuichi; Sasaki, Jun'ya; Akiba, Ryojiro
Abstract: The existence of a platform at the stratosphere is expected to be the role to gain a foothold in space. When the platform is employed airship in, it is transported by advection due to its light-weight body. Thereupon, a mooring of platform is reasonable in order to incarnate fixed-point platform. Conception of a captive platform system is similar to the Rockoon one which rendered remarkable services for the space observation of the early days. Therefore, the application of captive platform system to the launch site is highly expected in order to realize the space transportation system with a large quantity and high frequency. In this study, the motion of a captive platform system constructed from an airship and a tether is analyzed in order to ensure that the motion of a captive platform system is practically incarnated. Moreover, the sensitivity of aerodynamic performance of the airship is observed. Consequently, the practically incarnated motion of a captive platform system has been identified under the condition of the storm environment. Furthermore, the reduction of the advection distance driven away by the storm has been quantitatively indicated under the different condition of aerodynamic performance of the airship.